2020
DOI: 10.21315/aos2020.15.1.427
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Property of Synsepalum dulcificum Leaves Aqueous Extract against Oral Pathogens and its Chemical Compounds

Abstract: Synsepalum dulcificum (S. dulcificum) commonly known as "miracle fruit" because its berries have the capability to modify sour taste to the sweet taste when eaten. Beside the berries, S. dulcificum leaves were also known to possess biological properties such as antioxidant, antimutagenic and antidiabetic activities. However, the study of its antimicrobial activity against oral pathogen is still lacking. Thus, this study aimed to evaluate the antibacterial activity of its leaves against cariogenic bacteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The preliminary phytochemical analysis showed that Synsepalum dulcificum (Schumach. & Thonn) Daniell pulp contained saponin, flavonoids, tannin, alkaloids, glycosides, phenol, resins, terpenoids, steroids, and anthraquinones and cyanogenic glycosides (Ibrahim et al, 2020;Awotedu et al, 2021). The isolated compounds from Synsepalum dulcificum (Schumach.…”
Section: Chemopharmacological Potential Of Synsepalum Dulcificummentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary phytochemical analysis showed that Synsepalum dulcificum (Schumach. & Thonn) Daniell pulp contained saponin, flavonoids, tannin, alkaloids, glycosides, phenol, resins, terpenoids, steroids, and anthraquinones and cyanogenic glycosides (Ibrahim et al, 2020;Awotedu et al, 2021). The isolated compounds from Synsepalum dulcificum (Schumach.…”
Section: Chemopharmacological Potential Of Synsepalum Dulcificummentioning
confidence: 99%
“…The antifungal action was conveyed by the attack of cell wall and demolition of spores thus leading to intracellular constituent outflow and eventually death (Lateef et al, 2016). Recent study evaluated the antimicrobial effects of the leaves of S. dulcificum (Ibrahim et al, 2020). The study showed that the activity of S. mutans and S. sobrinus have been inhibited by the water extract of S. dulcificum leaves.…”
Section: Antimicrobial Potentialmentioning
confidence: 99%